SISTEM PENGELOLAAN PERSEDIAAN PADA PT BENDORO KREASI INDONESIA, JAKARTA - Enggun Gunawan; Rizky Putra Ramadhan (POLITEKNIK LP3I JAKARTA, 2024)
The inventory management system at PT. Bendoro Kreasi Indonesia is good enough. This can be seen from the existence of inventory management procedures that start from the arrival of inventory to the production of products. Likewise, the procedure is in accordance with the existing system, namely with a clear separation of functions between the operational department along with finance and marketing, as well as recording and reporting to the President Director with supporting documents. The inventory management system still has several weaknesses, namely in stock card recording or Daily Stock which uses manual recording which can still be improved. So that later there will be no mistakes and mistakes at the time of stock recording.